Efeito da privação parcial do sono e da fadiga mental no desempenho de atletas treinados de voleibol de praia - Barbosa, Bruno Teixeira (2023)
Mental fatigue (MF) and sleep restriction/deprivation (SR/SD) impair athletes’ perceptual-cognitive and physical performance in the most varied sports. Studies that evaluate the effects of combined MF and SR, that individualize the cognitive load and the duration of SR, and which analyse the perceptual-cognitive and physical performance of beach volleyball athletes from ecological tests are necessary. This study aims to analyse the effects of SR and MF, combined and isolated, on perceptual-cognitive and physical performance in trained beach volleyball athletes. Fourteen trained beach volleyball athletes participated in the study (12 men; 17.6±1.5 years). It is an experimental, crossover, and randomized study of repeated measures which implemented four experimental conditions: a) Control (CT), b) MF, c) SR, and d) SR+MF. MF was induced by the incongruous Stroop task, and the volunteers’ sleep activity was monitored for eight consecutive nights. Cognitive load and SR duration were individualized. Compliance with SR was monitored using an online form, filled in at 15-minute intervals for the duration of the SR. Physical performance was measured by a series of 50 jumps with countermovement with 5-second intervals between each jump performed at maximum effort, and perceptual-cognitive performance was evaluated via visuomotor tests with light emitting diode (LED) lights that simulated defensive and blocking actions in beach volleyball. The primary outcomes of the study were analysed by one-way ANOVA analysis of variance (condition [4] x moment [1]), and Bonferroni’s post-hoc was applied to locate any statistically significant differences. Continuous data are presented as mean and standard deviation, and categorical data as absolute and relative values. The SR condition caused slower responses in the “faster” (p=0.02; Cohen’s d=1.12; SR: 1562.14±109.06 ms vs CT: 1440.71±101.41 ms) and “mean” reaction time (RT) (p=0.02; Cohen’s d=1.13; SR: 1874.29±144.63 ms vs CT: 1727.14±113.30 ms) of the defence visuomotor test compared to CT, and the SR+ MF condition showed impairment in the “mean” RT (p<0.01; Cohen’s d=1.38; SR+MF: 1906.43±133.45 ms vs CT: 1727.14±113.30 ms) of the same test compared to CT. It was observed that the SR+MF condition impaired the “mean” RT (p=0.04; Cohen’s d=1.06; SR+MF: 722.14±100.09 ms vs CT: 631.42±82.17 ms) and “performance index” (p=0.02; Cohen’s d=1.18; SR+MF: 0.14±0.02 a.u vs CT: 0.16±0.02 a.u) for the visuomotor blocking test compared to CT. Physical performance was not impaired by any experimental condition. It is therefore concluded that SR, isolated and combined with MF, impairs the perceptual-cognitive performance of trained beach volleyball athletes; however, the damage of SR combined with MF do not overlap with those observed in SR when isolated. 17 Additionally, physical performance was not impaired by either MF or SR in beach volleyball-trained athletes.